Effect of surface orientation on the corrosion behavior of Ni-based single-crystal alloy in a simulated marine atmosphere at 750 °C - Tiancheng Cui; Shujiang Geng; Minghui Chen; Fuhui Wang (Journal of Materials Research and Technology)
DD5 single-crystal alloy samples with different surface orientations were obtained by machining the alloy ingot perpendicular (PP) and parallel (P), respectively, to its solidification direction (SD). The corrosion behaviors of the PPSD and PSD alloy samples were investigated in the atmosphere of moist air + NaCl aerosol at 750 °C. Results showed that during initial corrosion, γ′ phase developed a thin NiO layer with Al internal corrosion product. However, a NiO nodule with an internal Cr2O3 layer was formed on γ phase. As corrosion progressed, the corrosion product gradually grew to a NiO/(Al, Cr)2O3 bilayer, accompanied by internal corrosion consisting of Al2O3. It was also found that the PSD sample with a lower fraction and smaller size of γ’ phases exhibited better corrosion resistance than the PPSD sample. The effect of alloy surface orientation on the corrosion mechanism was discussed.